Penyuluhan HIV-AIDS pada Masyarakat Kelurahan Tumampua, Kecamatan Pangkajene, Kabupaten Pangkep - Balqis Balqis; Fhatira Nurul Ramadhany; Ardayanti Asmudin; Gabryella Laura Mongan; Inayatul Izzah (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Human Immunodeficiency virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) until now have become global public health problems. Community service activities related to HIV/AIDS are related to the Sustainable Development Goals (SDGs), namely to achieve health and well-being for all people. Based on data from the Pangkajene Health Center in 2022 there are 3 HIV/AIDS sufferers in the Tumampua Village, therefore it is necessary to carry out counseling to prevent an increase in HIV/AIDS sufferers while at the same time conducting health checks on the Tumampua Village community. The purpose of this service is to increase the knowledge and attitudes of the general public in the Tumampua Village regarding the prevention and control of HIV/AIDS, as well as the stigma and discrimination towards the people living with HIV/AIDS (PLWHA). This service is carried out in several stages, namely the preparation stage, the implementation stage, and the evaluation stage. Evaluation of HIV/AIDS counseling using Pre-Test and Post-Test questionnaires distributed to the community. The data analysis technique used is the Wilcoxon test. The results of statistical tests showed that HIV/AIDS counseling increased the knowledge and attitudes of the people in the Tumampua Village with 10 knowledge questions and attitude statements each.